2013
DOI: 10.1021/am403498q
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Reset in the Resistance Switching of the Al/TiOx/Cu Structure

Abstract: Two-step reset behaviors in the resistance switching properties of the top Al/TiOx/bottom Cu structure were studied. During the electroforming and set steps, two types of conducting filaments composed of Cu and oxygen vacancies (Cu-CF and V(O)-CF) were simultaneously (or sequentially) formed when Al was negatively biased. In the subsequent reset step with the opposite bias polarity, the Cu-CFs ruptured first at ~0.5 V, and formed an intermediate state. The trap-filled V(O)-CFs were transformed into a trap-empt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 25 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Therefore, in this work, only the NFSs were focused on afterward. Besides, in one of the previous works of the group of Shao et al, a Cu CF and a Magnéli phase CF were simultaneously formed when the Cu electrode was positively biased in the Al/200 nm thick TiO x /Cu memory cell. In that case, the TiO x film was reactively sputtered using a metal Ti target, making the structure quite porous.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, in this work, only the NFSs were focused on afterward. Besides, in one of the previous works of the group of Shao et al, a Cu CF and a Magnéli phase CF were simultaneously formed when the Cu electrode was positively biased in the Al/200 nm thick TiO x /Cu memory cell. In that case, the TiO x film was reactively sputtered using a metal Ti target, making the structure quite porous.…”
Section: Resultsmentioning
confidence: 89%
“…These diverse types of switching behaviors are ascribed to the rich chemical nature of the TiO 2 containing numerous Magnéli phases composed of Ti n O 2 n −1 ( n = 3, 4, 5…) and the relatively easy V O formation in the TiO 2 matrix. It has also been reported that TiO 2 plays the role of an electrolyte in the Al/TiO 2 /Cu ReRAM structure, where the ECM was mediated by the normal conical‐shaped Cu CF. These findings mean that TiO 2 is a highly intriguing material for various ReRAM applications, but they also imply that the involvement of mechanisms other than ECM can interfere with the resistance switching in the presumably ECM cell, such as the Pt/TiO 2 /Cu devices in this work.…”
Section: Introductionmentioning
confidence: 90%
“…However, as the resistance-switching random access memory (RRAM) is becoming one of the leading contenders for the next-generation non-volatile memory, SiO 2 along with other highly diverse metal oxides were tested as active resistance-switching (RS) layers. Several transition metal oxides (TMOs), such as TiO 2 , NiO, Ta 2 O 5 , and HfO 2 , have been tested as RS layers because the multi-valence nature of the transition metals would render the RS in these materials easily achieved 1 2 3 4 . Additionally, the so-called voltage-time dilemma from typical RS materials triggered interest in finding alternative RS materials, and several groups had tested SiO 2 5 6 7 .…”
mentioning
confidence: 99%
“…20 To obtain multi-level states in this case, a thin film of 3 nm AlO x with high bandgap (9 eV) 21 is used to increase R HRS and hinder hole injection from Al(TE). For Al/AlO x /VO x /Cu device, segmented I-V characteristics can be observed in set/reset process, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%